Development of A Diagnostic Test Instrument for Understanding Botanical Concepts for Biology Education Students - Putri Alfania Rizkiatul Jannah; Mucharommah Sartika Ami (APPLICATION: Applied science in Learning Research, 2023)
The aim of this study was to describe the feasibility of a diagnostic test instrument that was developed based on expert judgment, validity test, and reliability test. This development research refers to the Borg & Gall model, but is limited to the fifth stage. The steps taken were: research and information collection, planning, developing preliminary form of product, preliminary field testing, and revising main product. The instrument prototype was validated by botanist and biology education expert. The prototype that has been validated was then revised and tested on 36 biology education students who have taken a botany courses. Test results were then used to measure the validity and reliability of the instrument. The validity of the instrument was tested with the Pearson Product Moment formula and t test. Instrument reliability was tested with the Spearman-Brown formula. The results of the study revealed that the developed diagnostic test instrument was feasible according to expert judgment. Nine items were valid and reliable, while one item was not valid.